The taxonomic revision of Asian Aristolochia (Aristolochiaceae) IV: lectotypification of A. caulialata, with a new species from Yunnan, China—A. pseudocaulialata - Zhu, Xin-Xin; Liao, Shuai; Liu, Ji-Nan; Zhang, Chan; Ma, Jin-Shuang (Phytotaxa, 2018)
A taxonomic revision of A. caulialata is carried out in present study. It is lectotypiﬁed and epitypified, and the description of its leaf and inflorescence is revised. A new species, A. pseudocaulialata, from Yunnan, China, is also described and illustrated here. It is similar to A. caulialata in the shape of limb and color of throat, but can be distinguished by morphology of lamina and lobes of limb, and the length of anthers and gynostemium. The new species is also compared with A. faviogonzalezii and A. kwangsiensis, as they all have broadly ovate to suborbicular lamina. Whereas, A. pseudocaulialata differs from A. faviogonzalezii in the shape of limb, color of throat, and the length of capsule; differs from A. kwangsiensis in the color of limb, type of processes on the limb, the size of throat, and the length of capsule.